Next-Generation Sequencing (NGS) in non-small cell lung carcinoma: A real-world experience in the public health system of Galicia (Northwest Spain) - Ihab Abdulkader-Nallib; José Manuel Cameselle-Teijeiro; Iván Lesende-Rodríguez; Raquel Pérez-Becerra; José Ramón Antúnez-López; Jorge García-González; Luis León-Mateos; María Sánchez-Ares (PLoS ONE, 2025)
The validation of several predictive biomarkers has improved the clinical outcomes of non-small cell lung carcinoma (NSCLC) patients. Single tests do not cover the mutational co-occurrences, so they do not detect other alterations, which in many cases are responsible for disease progression. We describe the development and implementation of a customized next generation sequencing (NGS) panel. We analyzed 236 formalin-fixed paraffin-embedded (FFPE) NSCLC samples from the Clinical University Hospital of Santiago de Compostela (Galicia, Northwest Spain) in 2020. Detection of EGFR, KRAS, NRAS, BRAF mutations and ALK, ROS1 rearrangements were determined by real-time polymerase chain reaction (RT-PCR), immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH). These results were compared with those obtained by the NGS panel to evaluate the performance of the NGS method and to identify potential novel mutations. Ten discrepancies between NGS and the orthogonal methods were found: 2 cases in the EGFR gene, 1 in the KRAS gene, 5 in the BRAF gene and 2 in the ALK gene. The most prevalent pathogenic alterations detected by NGS were: TP53 (48.7%), KRAS (23.7%), STK11 (9.7%), EGFR (8.5%), PIK3CA (5.5%), CDKN2A (4.7%), BRAF (3.4%) and MET exon skipping 14 (3%); rearrangements were found in ALK and RET (3.5% and 1.7%, respectively). 41.5% of NSCLC patients are harbored co-occurring mutations. Our findings confirmed the robustness, sensitivity and specificity of NGS compared to conventional approaches. NGS has a role not only in the detection of actionable alterations (including concurrent mutations), but also in stratifying patients for therapy.